Fatal interstitial lung disease caused by Panitumumab-containing chemotherapy regimen - Al-asadi, Osamah (Ecancermedicalscience, 2018)
Fatal interstitial lung disease (ILD) is one of the rare side effects of Panitumumab. Both fatal and non-fatal ILD have been reported mainly in the Japanese population. We report a case of a nonsmoking Caucasian man with the diagnosis of metastatic rectal cancer (K-RAS wild-type) who developed fatal ILD after receiving a Panitumumab-containing chemotherapy regimen. He initially presented with a locally advanced rectal cancer (T3N2M0) for which he received neoadjuvant chemoradiotherapy. Before the rectal surgery, he was found to have liver metastases which were considered potentially resectable. The decision was to delay the rectal surgery and to start systemic treatment. He was started on Modified De Gramont regimen (folinic acid and fluorouracil) plus Oxaliplatin with Panitumumab. Six months later, he underwent rectal surgery which showed a complete response. He continued on systemic treatment while awaiting liver metastasectomy. After three courses of Modified De Gramont plus Oxaliplatin with Panitumumab, he was admitted with few days’ history of increasing shortness of breath. High-resolution computed tomography of the lungs showed the features of interstitial pneumonitis. Despite receiving appropriate treatment, he continued to deteriorate and died due to respiratory failure.